Dinámica del crecimiento, sobrevivencia y calidad de una plantación de la especie promisoria Caryodendron orinocense H. Karst “metohuayo” (euphorbiaceae), Puerto Almendra, Loreto. 2023 - Sangama Ampuero, Dorita Francisca (2023)
The study was conducted at the facilities of the Forestry Research and Teaching Center CIEFOR "Puerto Almendra" and the project "Provenance trials of forest and agricultural species of the Peruvian Amazon" attached to the National University of the Peruvian Amazon (UNAP) through the Faculty of Forestry Sciences, located in the district of San Juan Bautista, province of Maynas, Loreto region. The main objective was to know the dynamics of growth, survival and quality of a plantation of the promising species Caryodendron orinocense H. Karst "metohuayo" (Euphorbiaceae), Puerto Almendra, Loreto. The type of research was analytical, cross-sectional, prospective, quantitative approach, non-experimental design. The sample consisted of 100 individuals of Caryodendron orinocense H. Karst "metohuayo" included in a plantation of 0.5 hectares with a distance of 5 meters between plants, installed in 2021. The results show that the greatest increase in diameter was recorded in subplot 2, with a 1.87 cm increase at the end of the evaluation period. The greatest increase in height occurred in subplot 1, registering 101.57 cm increase at the end of the evaluation period. On the other hand, 81% of metohuayo plants survived at the end of the evaluation period, while mortality reached 19% respectively. Finally, according to the coefficient of variation of the number of plants per hectare, the value of 11.12% indicates that the plantation has an "acceptable" quality.